IMPLEMENTATION OF SUPPLY CHAIN MANAGEMENT FOR PRODUCT MANAGEMENT AT BAKTI JAYA STORE - Bayu Rahman; Fauriatun Helmiah; Mustika Fitri Larasati (STMIK Royal, 2024)
Abstract: Toko Bakti Jaya is one of the shops in Kisaran which is engaged in selling cake and food ingredients. Currently, the store is still managing product inventory manually by recording the number of incoming goods based on order records. Stock counting is done by looking directly at the warehouse, which causes difficulties in accurately monitoring stock and risks of shortages or excess stock. These constraints can affect customer satisfaction and store operations. This study aims to improve the efficiency of product inventory management at Bakti Jaya Stores by implementing a technology-based and information-based Supply Chain Management system. The research method is a qualitative method, with data collection techniques through interviews with informants, conducting field observations, and also obtained from literature studies. This research produces a product stock management information system using Supply Chain Management that connects Bakti Jaya Stores with suppliers to maximize coordination between stores and suppliers, facilitates control of the flow of stock availability in stores, and makes it easier for store owners to make decisions related to purchasing and procuring goods by providing accurate inventory analysis and real-time product stock information. Keywords: management; stock; suppliers; supply chain management Abstrak: Toko Bakti Jaya adalah salah satu toko yang ada di Kisaran yang bergerak dalam bidang penjualan bahan kue dan makanan. Saat ini, toko tersebut masih mengelola persediaan produk secara manual dengan mencatat jumlah barang masuk berdasarkan catatan pemesanan. Penghitungan stok dilakukan dengan cara melihat langsung gudang, yang menyebabkan kesulitan dalam pengawasan stok secara akurat dan berisiko terjadi kekurangan atau kelebihan stok. Kendala tersebut dapat mempengaruhi kepuasan pelanggan dan operasional toko. Penelitian ini bertujuan untuk meningkatkan efisiensi pengelolaan persediaan produk di Toko Bakti Jaya dengan menerapkan sistem Supply Chain Management berbasis teknologi dan informasi. Metode penelitiannya ialah metode kualitatif, dengan tehnik pengumpulan data melalui wawancara kepada narasumber, melakukan observasi ke lapangan serta juga didapat dari studi literature. Penelitian ini menghasilkan Sistem Informasi pengelolaan stok produk dengan menggunakan Supply Chain Management yang menghubungkan Toko Bakti Jaya dengan para supplier dapat memaksimalkan koordinasi antara toko dengan supplier, memudahkan pengendalian aliran stok ketersediaan barang di toko serta memudahkan pemilik toko membuat keputusan terkait dengaan pembelian dan pengadaan barang dengan menyediakan analisis persediaan yang akurat dan informasi stok produk yang real time. Kata kunci: pengelolaan; stok; supplier; supply chain management